KONDISI LAHAN PASANG SURUT KAWASAN RAWA PENING DAN POTENSI PEMANFAATANNYA - Euthalia Hanggari Sittadewi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2008)
The tidal land in Rawa Pening’s region is land that has been formed as caused of up and down water level process of Rawa Pening’s lake. The wide of tidal land that can be used are fluctuated beetwen dry and rainy seasons. The main used of tidal land is for rice field. The wide of tidal land that can be used for rice field beetwen elevation + 462,30 m and +463,30 m are 812 Ha, between elevation + 462,05 m and +462,30 are 218,51 Ha. There are some species of paddy that has been cultivated in that area, are IR-64, GH barito, ciliwung, cisadane, membramo and mentik. Mean of paddy yield is about 2,5 – 5 ton/ Ha.